Tomatoes - Marr, Charles W.; Tisserat, Ned; Bauernfeind, Robert; Gast, Karen L. B. (My University, 1995)
This publication is for commercial vegetable production, specifically the production of tomatoes in Kansas.
MF1124_1995_01
Keywords: MF1124; Crops; Fruits and Vegetables; Equipment and Structures; MF